Chronic cyclic vagus nerve stimulation has beneficial electrophysiological effects on healthy hearts in the absence of autonomic imbalance. Issue 9 (12th May 2016) - Lee, Steven W.; Li, Qinglu; Libbus, Imad; Xie, Xueyi; KenKnight, Bruce H.; Garry, Mary G.; Tolkacheva, Elena G.
Abstract: Cardiovascular disease degrades the regulatory function of the autonomic nervous system. Cyclic vagus nerve stimulation (VNS) is an already FDA‐approved therapy for drug‐resistant epilepsy and depression, and has been shown to normalize autonomic function and improve objective measures of heart function and subjective measures of heart failure symptoms. However, it remains unclear whether VNS may induce negative effects in patients with potentially healthy hearts where VNS can be used for epileptic patients. Hence, this study aims to investigate the effects of VNS on the hearts of healthy rats with normal autonomic balance. Sprague–Dawley rats were implanted with stimulators and randomized to either Sham or VNS groups. Rats in VNS group received 10 weeks of chronic intermittent VNS via stimulation of the right cervical vagus nerve. Echocardiography was performed at Baseline (prior to VNS), Week 2, and Week 9. After 10 weeks, high‐resolution optical mapping was performed in ex vivo perfused hearts to evaluate the electrophysiological remodeling that occurs in the heart as a result of the VNS therapy. Chronic VNS modified the electrophysiological properties of healthy rat hearts by reducing the action potential duration at 50% (APD50 ) and 80% (APD80 ) repolarization. Chronic VNS also affected the restitution properties of the heart at the APD50 level and increased myocardial conduction velocity (CV). VNS did not induce any significant changes to ventricular ejection fraction (EF) and spatial dispersion of APD, thus indicating that VNS did not negatively affect cardiac function. VNS also reduced the susceptibility to ventricular arrhythmias (ventricular fibrillation [VF] and ventricular tachycardia [VT]) during ex vivo programmed electrical stimulation. In summary, chronic application of cyclic VNS induces changes to the electrophysiological properties of healthy rat hearts. The observed decrease in APD and increase in CV suggest that the beneficial effects of VNS do not require the presence of existing autonomic imbalance. Abstract : The administration of chronic intermittent vagus nerve stimulation (VNS) induces beneficial electrophysiological changes to a normal, healthy rat heart; thus, rendering the hearts less vulnerable to inducible arrhythmias. These results also suggest that VNS does not require the existence of autonomic imbalance to generate its positive effects.